THE LONG RECESSION AND ECONOMIC CONSEQUENCES OF THE COVID-19 PANDEMIC - Tsoulfidis, Lefteris; Tsaliki, Persefoni (Investigación Económica, 2022)
ABSTRACT In this article, we argue the rate of profit in combination with the movement of the real net profits determines the phase-change of the economy in its long cyclical pattern. Since WWII, the US and the world economy have experienced two such long cycles. The pandemic COVID-19 has deepened a recession that has been already underway since 2007. The growth rates in the first post-pandemic years are expected to be high; however, soon after, the economies will find themselves back to their old recessionary growth paths. The onset of a new long-cycle requires the restoration of profitability, which can be sustained only through the introduction of ‘disruptive’ innovations backed by suitable institutional arrangements. LA LARGA RECESIÓN Y LAS CONSECUENCIAS ECONÓMICAS DE LA PANDEMIA COVID-19 RESUMEN En este artículo argumentamos que la tasa de ganancia, en combinación con el movimiento de las ganancias reales netas, determina el cambio de fase en el patrón del ciclo largo de la economía. Desde la Segunda Guerra Mundial Estados Unidos y la economía mundial han experimentado dos ciclos largos. La pandemia COVID-19 ha profundizado la recesión que ha estado en curso desde 2007. En los primeros años posteriores a la pandemia se espera que las tasas de crecimiento sean altas; sin embargo, inmediatamente después las economías retornarán a sus anteriores trayectorias de crecimiento recesivas. El inicio de un nuevo ciclo largo requiere de la restauración de la tasa de ganancia, que sólo puede sostenerse a través de la introducción de innovaciones “disruptivas” apoyadas por arreglos institucionales adecuados.